The Impact of Counseling in Patients with Chronic Obstructive Pulmonary Disease: Knowledge, Attitude, and Practice Outcome - Avinash Khadela; Dhaval B. Joshi; Bhavin Vyas; Ekta Patel (Journal of Integrated Health Sciences)
Background: The pharmacists can contribute to positive therapeutic outcomes by educating patients for rational use of medications. A chronic obstructive pulmonary disease (COPD) is one the most prevalent chronic respiratory diseases which requires continuous medication therapy. The clinical pharmacist can play an effective role through providing patient counselling to improve medication adherence and therapeutic outcomes. Aims and Objectives: The present study aims to assess the baseline levels of knowledge, attitude and practice of COPD patients and to study the impact of patient counselling on level of knowledge, attitude and practice with COPD patients. Materials and Methods: A total 90 patients (45 in the test group and 45 in control group) were enrolled in the study. A validated Knowledge, Attitude and Practice (KAP) Questionnaire was administered to both test and control group of patients at base line and at follow up (after 15 days) to assess the awareness regarding disease management. Patients in test group received counselling at visit and information leaflets were given. The control group of patients did not receive such counselling and information leaflets. Results: At the end of study the KAP scores of test group patients improved significantly (P<0.05), whereas no significant changes were observed in control group patients. We did not observed significant improvement in practice outcomes. However, patients counselling by a pharmacist improved overall KAP score. Conclusion: We conclude that pharmacist counselling may have an impact in improving the perception about disease and lifestyle change and thereby improving the Quality of life (QOL) of COPD patients.